Anticipating and Executing off Beat Pregnancies in Müllerian Duct Anomalies: A Case Series - Satyasri Koya; Krishnapriya Radhakrishnan; Sanjitha Ravikumar; Somika Kaul; Archie Desai (Tehran University of Medical Sciences, 2024)
Objective: Müllerian duct Anomalies (MDA) are rare but well-known entity. Most of the MDAs are asymptomatic, and are undiagnosed; However, MDAs may present with infertility, bad obstetric history or other associated anomalies which further fuel the suspicion of MDAs. This case series comprises of 6 problem-pregnancies, their course and management. Case report: Primigravida with bicornuate uterus presented at 23 weeks with hand prolapse, requiring hysterectomy. A G2P1L0 presented at 36 weeks with footling presentation, managed by a preterm CS. Primigravida presented at 24 weeks with Didelphys uterus with partial longitudinal vaginal septum, needing hysterotomy. Primigravida at 37 weeks presented with abruptio placenta, managed by CS. Conclusion: Though the incidence of MDAs is low, but the outcomes can be rather distressing for both mother and fetus. Once identified, adverse outcomes must be anticipated and prepared for, and these are best managed at tertiary hospitals. Apart from counselling we should also meticulously document, improve awareness regarding MDAs and their outcomes. Early diagnosis and timely management can hit the jackpot in terms of pregnancy outcomes.